THE CHANGE IN STRESS RESISTANCE OF THE STUDENTS WHEN APPLYING TRANSCRANIAL ELECTROSTIMULATION - A. Kh. Kade; S. K. Akhedzhak-Naguze (Кубанский научный медицинский вестник, 2018)
Aim.To determine the transcranial electrostimulation effect on stress resistance of students, according to N.V. Kirsheva, N.V. Ryabchikova test.Materials and methods. 127 medical students (50 boys and 77 girls aged from 19 to 22) were observed. All the students were practically healthy. They were divided into the main group (78 people) and the comparison group (49 people). The students of the main group underwent transcranial electrostimulation (TES): 22 people got 2 sessions a week, 56 people got 5 sessions a week. The level of stress resistance in the main group was determined according to N.V. Kirsheva, N.V. Ryabchikova test before and after TES. In the comparison group, the level of stress resistance was determined the same way. TESs were conducted with the Transair-03 apparatus. The results of the study were determined for the normal distribution using the computer program "STATISTIKA 6.0" and processed with parametric methods.Results. In the comparison group subjects had moderate and low levels of stress resistance. There were no significant changes in the levels of stress resistance in the initial state and a week later. After two TES sessions the number of students with average level of stress-resistance decreased by 3 people, and the number of students with high level of stress resistance increased by 3 people. There were no statistically significant differences in the level of stress resistance. During five TES sessions the level of stress resistance in 26 people increased from medium to high. Number of points after TES decreased by 10.3%, which indicated an increase in the level of stress resistance. No gender differences were taken into account. The interpretation of the test results by NV. Kirsheva, N.V. Ryabchikova showed high level of stress resistance in 13 subjects at a level "above average", "high" in 2 subjects. After 5 TES sessions, 15 subjects had "higher than average" level, 19 subjects had "high" level, 7 subjects had "very high" level.Conclusion. Thus, there is a reliable increase in stress resistance in practically healthy medical students of both sex at the end of the academic year after 5 TES sessions a week. Subjects who had medium and high levels of stress resistance before TES got high level of stress resistance after TESs, which also changed qualitatively: "proper high level" increased and "very high level" of stress resistance appeared.